Direct Visualization of Nanoconfinement Effect on Nanoreactor via Electrochemiluminescence Microscopy. (28th December 2022) - Huang, Xuedong; Li, Binxiao; Lu, Yanwei; Liu, Yixin; Wang, Shurong; Sojic, Neso; Jiang, Dechen; Liu, Baohong
Abstract: Nanoconfinement in mesoporous nanoarchitectures could dramatically change molecular transport and reaction kinetics during electrochemical process. A molecular‐level understanding of nanoconfinement and mass transport is critical for the applications, but a proper route to study it is lacking. Herein, we develop a single nanoreactor electrochemiluminescence (SNECL) microscopy based on Ru(bpy)3 2+ ‐loaded mesoporous silica nanoparticle to directly visualize in situ nanoconfinement‐enhanced electrochemical reactions at the single molecule level. Meanwhile, mass transport capability of single nanoreactor, reflected as long decay time and recovery ability, is monitored and simulated with a high spatial resolution. The nanoconfinement effects in our system also enable imaging single proteins on cellular membrane. Our SNECL approach may pave the way to decipher the nanoconfinement effects during electrochemical process, and build bridges between mesoporous nanoarchitectures and potential electrochemical applications. Abstract : Single nanoreactor electrochemiluminescence microscopy based on Ru@MSN realizes direct observation of nanoconfinement during electrochemical process which can bridges mesoporous nanoarchitectures and potential electrochemical applications. Long time decay and recover ability caused by nanoarchitecture are resolved. The nanoconfinement effects are stable even in complex biological conditions, offering excellent route for single biomolecule imaging.